To Grow a White Rose.... speaking of Cantú - Calderón-Fernández, Miguel Ángel (2021)
This essay brings to mind the practice of the school of Cantú (Costa Rica) which used to start every morning classes reciting the symbolic poem of José Martí and the steps of a child from his peasant hometown village up to reach the university classrooms. That child kept forever the musicality and criticism of the texts of the Cuban author, which shaped his life.